World's greatest sports stars - Anonymous (Uttar Pradesh : Wonder House, 2023)
A well-researched book, which celebrate the achievements of talented sports personalities who inspired generations with their talent, hard work and success. Age appropriate content, fun facts and bold illustrations will appeal to the curiosity of young inquisitive minds and help them develop their reading skill and general knowledge.
Keywords: Biographies -- Juvenile Literature; Greatest Leaders -- Juvenile Literature; Inspirational People -- Juvenile Literature; Powerful people -- Juvenile Literature